CAREER FUTURE OF FEMALE STUDENTS: A SECONDARY SCHOOL CASE - MIZRAK, Şeyma (SSD Journal, 2025)
The purpose of this research is to evaluate the effectiveness of the group guidance program designed to reduce students' career decision-making difficulties. In this regard, "Does the group guidance program prepared in the light of the literature have an effect on reducing the career decision-making difficulties of 8th grade female students?" The answer to the question has been sought. An experimental design with pretest, posttest, experimental and control groups was used in the research. Appointments were made randomly to form groups. The experimental and control groups of the research consist of female students (7 experimental groups, 7 control groups) attending the 8th grade in a secondary school in Yeşilyurt district of Malatya province in the 2024-2025 academic year. "Career Decision Making Difficulties Scale" (Bacanlı, 2008) was used to measure the career decision-making difficulty levels of the students participating in the research. The data of the research were analyzed in computer environment with the SPSS (Statistical Package for Social Sciences) package program, in accordance with the established hypotheses. Since the hypotheses are based on repeated measurements, two-way analysis of variance technique was used for mixed patterns in the analysis of the data. One of the factors is groups (experiment and control), while the other is measurements (pretest, posttest). It was determined that the Group*Measurement interaction had a significant effect (F (1-14) = 71.05, p < .05). In conclusion; The change between consecutive (repeated) measurements (pretest and posttest) (experimental and control) showed a significant difference according to the treatment groups.